ANTIOXIDANT ACTIVITY AND PHARMACOLOGICAL SCREENING OF TINOSPORA CORDIFOLIA (THUNB.) - KUMAR, AMIT; KUMAR, MANOJ; DANDAPAT , SUKUMAR; M. P. SINHA (The Bioscan, 2012)
The communication deals with the antioxidant activity of aqueous and methanolic extracts of Tinospora cordifolia (Thunb.) stem, along with the phytochemical, pharmacological and nutritive properties. Methanolic extract showed good antioxidant efficacy compare to the BHA standard. Reducing power of the extract showed concentration dependence. Lipid peroxidation inhibition was not significant. Methanolic extract showed significant DPPH radical scavenging activity (EC50 = 0.5 mg/mL), while the superoxide radical scavenging activity of the methanolic extract was mild and showed concentration dependence. The phytochemical analysis showed low amount of total ash content, i.e. 11.3 ± 1.4 mg/g. Total phenol, tannin and flavonoids contents were 17.3 ± 0.4, 13.8 ± 0.5 and 6.5 ± 0.2 mg/g respectively which fall under moderate range. Crude fiber and moisture contents (231 ± 3.2 and 214 ± 5.3 mg/g respectively) as well as carbohydrate content (184.1 ± 5.2 mg/g) and nutritive value (1.46 ± 0.3 cal/g) were significantly high. T. cordifolia stem showed high swelling and foaming indices, 400 ± 3.5% and 111.12 ± 2.1% respectively, which is an indication of good drug release characteristics. Present findings suggest Tinospora cordifolia as potential source of natural antioxidant, fiber and nutrient content in food, fodder and pharmaceutical industries.